On evaluating the possible hazard of soil contamination in arid regions using statistical analysis and GIS techniques - El-Sorogy, Abdelbaset S.; Al-Kahtany, Khaled; Shokr, Mohamed S.; Alharbi, Talal; de Larriva, Jose Emilio Meroño (Frontiers in Earth Science, 2025)
IntroductionHeavy metals (HMs) contamination of soil is gaining a lot of attention globally because of its apparent toxicity and potential risks to local populations. Therefore, the first stage of high-efficiency pollutant degradation and sustainable utilization is the evaluation of soil heavy metal distribution, sources, and environmental dangers. However, details regarding the sources of heavy metals and the degree of contamination in specific soils in the Al Qassim region of Saudi Arabia are lacking.MethodThus, the present study assessed the environmental risk of Arsenic (As), Cobalt (Co), Chromium (Cr), Copper (Cu), Iron (Fe), Nickel (Ni), Lead (Pb),Vanadium (V), and Zinc (Zn) in the central portion of the Al Qassim region, Saudi Arabia using a range of contamination indices and multivariate approaches. Thirty-two surface soil samples were gathered for analysis. The Normalized Difference Vegetation Index (NDVI), and land use land cover (LULC) maps were computed using a sentinel 2 image of the research area from Google Earth Engine (GEE).Results and discussionThe potential ecological risk index (PERI) and the modified degree of contamination (mCd) averages were 26.6 and 0.6, respectively, hence all soil samples were deemed low-contaminated. According to the multivariate analysis, these HMs primarily originate from natural rocks except for Zn which may originate from an anthropogenic source but is still in a safe concentration. Because the research region is include a lot of cultivation activates, as indicated by the NDVI status and LULC map, The results of the spatial distribution maps of pollutants and their concentrations can be used by decision-makers to guide future HMs concentration monitoring in the study area, to avoid any potential future soil contamination as well as to improve human health, worldwide food security, and the accomplishment of the Sustainable Development Goals (SDGs).